THE EFFECT OF GAMEPLAY PATENTS BY NINTENDO ON THE GAME INDUSTRY BASED ON A STUDY OF GRANTED PATENT US12403397 - Radian Suparba, (Proceeding International Conference on Social Sciences, 2026)
The phenomenon of Intellectual Property Rights has grown rapidly, currently the separate grouping of IPR is no longer considered able to protect innovative works, so the idea emerged by including or mixing elements of IPR categories with others, such as computer programs can be objects for patent registration because they have met the requirements for patents, namely new, have inventive steps and are applied in the Industry. Currently, patents registered by Nintendo and the Pokemon Company are a concern for video game makers and gamers, this is because there are issues of patents that have been granted or legally protected by patents and there are already certificates that include ownership of gameplay or how to play video games related to Pokemon games in the form of how to catch monsters, ride monsters and issue or summon monsters (monster summoning). This will force game companies to change the game play system to avoid patent lawsuits from Pokemon and Nintendo companies. For gamers and game makers, this is a concern because it is assumed that it will affect other games, especially indie games and gamer satisfaction in playing games will be reduced due to patents from Nintendo and Pokemon.